Penggunaan Cairan Magnetorheologi untuk Meningkatkan Kinerja Body Armor - Awalia Yasin, Nurin Krisfina; Aritonang, Sovian; Murniati, Riri (Fakultas Teknik UMSU, 2024)
In this journal, we will explain the use of Magnetorheological fluid (MRF) in body armor. The use of MRF material was chosen because its properties can be adjusted using external magnetic forces. The durability of the material structure will be tested using a 9 mm projectile and will be tested using a puncture. In tests carried out with projectiles, the MRF structure will experience a reduction in depth. Testing using a puncture will change the MRF structure to deform by 30% of the normal structure. The application of MRF to kevlar can increase energy absorption and can reduce the effects of bullet impacts. These results show quite good results compared to using other materials in making Kevlar. Apart from that, several advantages of MRFs from graphene in making body armor are also explained. This advantage was obtained from testing the mechanical properties of graphene against several other materials.